2012
DOI: 10.7314/apjcp.2012.13.3.1059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Overall Survival in Patients With Metastatic Colorectal Carcinoma Treated With Vascular Endothelial Growth Factor-Targeting Agents

Abstract: Objective: Angiogenesis represents a key element in the pathogenesis of malignancy. There are no robust data on prognostic factors for overall survival (OS) in patients with metastatic colorectal cancer treated with vascular endothelial growth factor (VEGF)-targeted therapy. The present study was conducted to establish a prognostic model for patients using an oxaliplatin-based or irinotecan-based chemotherapy plus bevacizumab in metastatic colorectal cancer. Methods: Baseline characteristics and outcomes on 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…However, findings from the vatalanib study suggested that there was a trend towards better clinical outcomes in the subgroup of patients with high LDH (Van Cutsem et al , 2011b) and, together with our findings, indicate that high baseline LDH levels may be associated with improved patient outcomes. However, such findings have not been demonstrated in previous studies with bevacizumab (Suenaga et al , 2011; Scartozzi et al , 2012; Cetin et al , 2012). These inconsistencies may indicate that, rather than overall LDH expression, levels of specific isoforms of LDH may have a predictive influence on clinical outcomes.…”
Section: Discussioncontrasting
confidence: 71%
“…However, findings from the vatalanib study suggested that there was a trend towards better clinical outcomes in the subgroup of patients with high LDH (Van Cutsem et al , 2011b) and, together with our findings, indicate that high baseline LDH levels may be associated with improved patient outcomes. However, such findings have not been demonstrated in previous studies with bevacizumab (Suenaga et al , 2011; Scartozzi et al , 2012; Cetin et al , 2012). These inconsistencies may indicate that, rather than overall LDH expression, levels of specific isoforms of LDH may have a predictive influence on clinical outcomes.…”
Section: Discussioncontrasting
confidence: 71%
“…The analysis of several studies have emphasized the importance of several clinical parameters such as age (Aslam et al, 2010), white blood cell, liver transaminases (Kemeny et al, 1983), haemoglobin (Graf et al, 1994), mean platelet volume (Tuncel et al, 2014), neutrophil/ lymphocyte ratio (Dirican et al, 2014;Wen-Zhuo et al, 2014), serum alkaline phosphatase (Chibaudel et al, 2003), serum γ-glutamyl transpeptidase (Wen-Zhuo et al, 2014), serum lactate dehydrogenase (Cetin et al, 2012), serum albumin (Tebbutt et al, 2003), tumor markers like CEA (Wen-Zhuo et al, 2014) and CA 19-9 (Katoh et al, 2008), ECOG PS (Galizia et al, 2008), primary tumor site (Bajwa et al, 2009), adjuvant chemotherapy (Katoh et al, 2008), pathological grade, number of metastatic sites (Yun et al, 2007), volume of liver metastases (Kleespies et al, 2009), metastasectomy (Settmacher et al, 2011) and state of KRAS/NRAS/BRAF mutation and PTEN loss (Tejpar et al, 2012;Yokota, 2012;Atreya et al, 2013) in the metastatic setting. Among these factors, patients with a V600E BRAF mutation have a poor prognosis which only settled in the guidelines (Bokemeyer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In Lebanon among 36 patients with CRC, no significant difference was noticed between for VEGF level between normal and patients group and also between different age groups and both genders (Greene, 2002). Also in another study, it was shown that Serum LDH and neutrophil levels were the main prognostic factors in predicting survival, followed by progression free survival and VEGF (Cetin et al, 2012).…”
Section: Discussionmentioning
confidence: 90%